PENGARUH MOTIVASI BERPRESTASI DAN KREATIVITAS GURU TERHADAP KINERJA GURU SD SE-GUGUS I UNIT PELAKSANA TEKNIS DINAS (UPTD) TAMPAN KOTA PEKANBARU - Aslindawati Aslindawati; Caska Caska; Mahdum Mahdum (Universitas Riau, 2017)
This study aims to investigate the influence of variables (1) achievement motivationon teacher performance, (2) creativity of teachers on teacher performance, (3) the achievementmotivation and creativity of teachers together on teacher performance. Respondents areelementary school teachers throughout the first cluster of Technical Implementation Unit (UPTD)Handsome Pekanbaru totaling 114 obtained by simple random sampling technique. Data collectedthrough questionnaire as a research instrument. Analysis of the data used is descriptive analysis,inferential statistical analysis and hypothesis testing. Instrument reliability coefficient is calculatedusing Cronbach alpha. In the partial results show the positive influence of achievement motivationon teacher performance of 0,537, and a positive influence between the creativity of teachers onteacher performance amounted to 0,397. While simultaneously the positive influence ofachievement motivation and creativity of teachers on teacher performance of 0,913.